STRENGTHENING THE TECHNOLOGY-BASED HOME INDUSTRY APPROPRIATE FOR EFFORTS TO IMPROVE THE WELFARE OF THE PEOPLE OF KADUKEMPONG VILLAGE - Khodijah, Ina; Jonathan, Julius Felix; Turmudi, Udi; Iroh, Iroh; Rahmawati, Septi Dwi; Ardiansah, Deden; Putri, Sofiya Asfira (Nindikayla Institute, 2024)
Thematic KKM results and Community Service in 2021 in Kadukempong Village, Padarincang Subdistrict, Serang Regency has significantly moved thecommunity economy. Of the various home industry-based economic activities that have been successfully identified and improved are the activities of the home industry of kagugu chips. From the identification and assistance that has been done, identified the following problems: (1) the low entrepreneurial ability of home industry actors, (2) the production process that has not implemented good manufacturing products (3) packaging is still not attractive and selling,and (4) marketing is still limited to orders. To help overcome these problems, thematic KKM conducts activities in the form of (1) entrepreneurial training for home industry players and the general public, (2) assistance in the production process with the application of good manufacturing products, (3) conducting training and mentoring in the design of home industry product packaging, (4) conducting mentoring and marketing training based on promotion and information technology. In carrying out its activities, this ThematicKKM cooperates with the Kadukempong Village government. The efforts that will be made refer to the basic strategy of village economic development to create an increasingly advanced, strong,and independent economic structure with its flagship sector, namely trade, small industry. Especially for small industries that are the base sector in economic activity in Kadukempong Village. The development of small industries in the broadest sense is directed at advanced economic activity, independent, environmental sustainability, and a driver for the development of other sectors. The expected externality of this Thematic KKM is: (1) the implementation of good manufacturing products in MSME actors ranging from the selection of rawmaterials, production processes, and post-production (2) the increasing quality of home industry product packaging based on simple technology, (3) the availability of msme product marketing promotion media online. (4) Increasing the welfare of the people of Kadukempong Village, especially the people in the location of this Thematic KKM. This activity was held in Kadu Kempong Village, Padarincang District, Banten Province, starting from July 14, 2021 to August 29, 2021 with 17 students.